SIMULATION OF THE DISTRIBUTION OF TEMPERATURE, STRESSES AND DEFORMATIONS DURING SPLINED SHAFTS HARDFACING - Nurzhanova, Oxana; Zharkevich, Olga; Bessonov, Alexander; Naboko , Yеlena; Abdugaliyeva , Gulnur; Taimanova, Gulnara; Nikonova, Tatyana (Journal of Applied Engineering Science, 2023)
This article describes the process of modeling the restoration operations of the destroyed segment of the spline and its complete restoration using modern methods, such as hardfacing in a protective gas environment with a consumable electrode. The ANSYS Workbench 19.2 software with an additional Welding Distortion and Moving Heat Source extension was used to simulate the process of hardfacing a damaged surface. The thermomechanical behavior of the deposited layer on the outer surface of the splined shaft is analysed. Dependences of the value of temperature fields on the parameters of the hardfacing mode in one and two passes depending on time are established. Dependences of residual stresses (0.413 - 239 MPa) and deformations (0.02 - 0.23 mm) in the process of semi-automatic hardfacing are determined. Experimental studies of samples during hardfacing were carried out for comparison with the geometry of the weld during modeling. The simulation results are in good agreement with the experimental data.
Keywords: hardfacing, temperature, stresses, deformation, spline